2005
DOI: 10.2109/jcersj.113.112
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ IR Spectral Measurement in Organic Matrix-Mediated Hydroxyapatite Formation

Abstract: L@}gbNXU±ÉaeénChLVAp^Cg`¬ßöɨ¯éÔOªõ»Ìêªè ²¡ö×EFJF¢Þ E ¶îrVÞ Þ EnLiEcOÞ Þ YAEZp¤C4638560 ¤m §¼Ã®sçRaeºui¡´226698 Þ ÈwZpU»@\ CRESTC3320012 éÊ §ìûs{¬ 418 Þ Þ¿EÞ¿¤@\C3050044 ïé §ÂÎsÀØ 11Organic templatedirected crystallization of hydroxyapatite (HAp) was studied insitu via Fourier transform IR external reection spectroscopy. Langmuir monolayer of arachidic acid was formed on a surface of simulated body uid, which possesses inorganic ion concentrations and a pH value almost equal to those of human blood plasma. Owi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Previous studies have found similar spectral features of carbonated HAP after SBF immersion of ePTFE samples grafted with MOEP in methanol [8] , in the aqueous phase of a two-phase system [9] as well as on a branched PMOEP film [34] . This finding also correlates with the FTIR spectrum obtained for the mineral formed in SBF on an arachidic acid Langmuir monolayer [35] and the precipitate formed in SBF when pH is kept constant during precipitation [36] . The intensity of the carbonate bands relative to the phosphate band is much higher for samples AA(0.3)-R and AA(1.3)-R and the carbonate band at 875 cm −1 is less pronounced in these samples compared to the two high graft extent samples.…”
Section: Resultssupporting
confidence: 83%
“…Previous studies have found similar spectral features of carbonated HAP after SBF immersion of ePTFE samples grafted with MOEP in methanol [8] , in the aqueous phase of a two-phase system [9] as well as on a branched PMOEP film [34] . This finding also correlates with the FTIR spectrum obtained for the mineral formed in SBF on an arachidic acid Langmuir monolayer [35] and the precipitate formed in SBF when pH is kept constant during precipitation [36] . The intensity of the carbonate bands relative to the phosphate band is much higher for samples AA(0.3)-R and AA(1.3)-R and the carbonate band at 875 cm −1 is less pronounced in these samples compared to the two high graft extent samples.…”
Section: Resultssupporting
confidence: 83%
“…It is very clear that the performances of crystals such as polymorphism and orientation strongly depend on the structure and property of film templates. On the other hand, Sato and Charych studied the structural changes of Langmuir film at air-water interface and they found that the structures of the organic films vary (dynamic molecular rearrangements) during the nucleation process [15,16]. However, structural change in an LB film template tuned by temperature has received little attention in the crystal growth field.…”
Section: Introductionmentioning
confidence: 99%